Pessoas com deficiências na Assembleia Nacional Constituinte (1987-1988): reivindicações no campo educacional - Amorim, Joyce Fernanda Guilanda de (2018)
This paper analyzes how the legal mechanisms for the education of people with disabilities in the National Constituent Assembly (ANC), 1987/1988, the historical moment that culminated in the Constitution of the Federative Republic of Brazil promulgation, on October 5th 1988, as well as the participation of people with disabilities and entities involved in public hearings in the Subcommittee of Black people, Indigenous Populations, People with Disabilities and Minorities, as well as the discussion on education in the Subcommittee on Education, Culture and Sports. The research was subdivided into four chapters: the first chapter is composed of the knowledge production, based on the research carried out using the keywords "Social Movements", "National Constituent Assembly" and "People with Disabilities" at Digital Databank of Thesis and Dissertations - BDTD, of the Brazilian Institute of Information in Science and Technology - IBICT; the second chapter dealt with the events during the civil-military dictatorship (1964/1965), the Brazilian Democratic Movement the performance in opposition to the Arena and the called by the Constituent; chapter three covers the end of the civil-military dictatorship, as well as the historical process that culminated in the indirect election of Tancredo Neves to president and José Sarney as vice president; the fourth chapter dealt with the civil Society profile that participated in the discussions on people with disabilities, its organization to elaborate the proposals presented at a public hearing in the Subcommittee on Blacks, Indigenous Populations, Disabled People and Minorities, in addition to the other constituent phases and works, with a view to articles aimed at the people with disabilities education and philanthropic institutions. As a research result, it was pointed out that many claims of people with disabilities were contemplated in the Constitutional text. It was found that the participation of Deputy Nelson de Carvalho Seixas influenced the process of some subjects for people with disabilities. It was noted the parliamentarians lack of knowledge about the proposals of these people discussed during the ANC, and that education became the right of everyone, the State and the family duty, as well as guaranteeing specialized educational service, preferably in the regular network of education.